Effects of internal control on the financial indicators of companies - Jovetić, Slavica; Ljubisavljević, Snežana; Karapavlović, Nemanja (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
The aim of the research presented in this paper is to measure the significance and importance of internal control (IC) in companies, as well as to identify differences relating to the significance and importance of IC based on the comparative analysis of the distinctive components of internal control. Thus, the research is organized in two parts. The first part includes the evaluation of the significance and importance of IC at the level of a company level, of individual transactions and of sub-processes; it also examines the impact of IC on the financial performance of a company, as well as the effects of certain IC elements related to the sub-processes on the overall significance of IC. The second part of the research is about identifying the existence of dissimilarities in terms of the significance and importance of IC in companies by the type of business entity (i.e. the legal form) and the type of business activity. In accordance with the stated objectives of the research, data analysis is performed by using the following statistical and econometric methods: regression analysis and hypothesis testing for equality of arithmetic means and proportionality. This paper presents the results of the first part of the research. Based on the created database containing the collected structural data, the results of surveys and the specified regression models, as well as the results of quantitative analyses and the derived conclusions on the statistical significance of the effects of the specified independent variables, it is possible to obtain valid information on the importance and significance of IC for a company's operations. The results and information obtained from the first part of the research and the results obtained after the application of the statistical and econometric analysis are contrasted by means of comparative analysis. The results of this research will facilitate obtaining sound scientific information to be used for strategic management, planning and decision-making at all levels of a company regarding the significance and importance of internal control
Argumenta Oeconomica, 2018, Nr 1 (40), s. 115-146
Keywords: internal control; cost efficiency; profitability; productivity